Legal requirements for school rules and disciplinary sanctions - Roos, R. (Koers, 2003)
The new educational dispensation has created some uncertainty regarding the application and formulation of school rules, lawful disciplinary measures and procedural requirements for discipline in schools. This contribution is aimed at providing a legal framework for lawful school rules, as well as for the interpretation and application of school rules. The legal framework is assessed from a reformational frame of reference, which includes taking a stand regarding the state and its functions. The discussion focuses on phenomena such as education, discipline and order. The requirements for lawful disciplinary measures are also addressed. The conclusion is that the drastic changes to the system afford Christian governing bodies and educators the opportunity to promote true discipleship within the parameters of the law.